The Reversal of Large Stock‐Price Decreases - BREMER, MARC; SWEENEY, RICHARD J. (Journal of Finance, 1991)
ABSTRACT Extremely large negative 10‐day rates of return are followed on average by larger‐than‐expected positive rates of return over following days. This price adjustment lasts approximately 2 days and is observed in a sample of firms that is largely devoid of methodological problems that might explain the reversal phenomenon. While perhaps not representing abnormal profit opportunities, these reversals present a puzzle as to the length of the price adjustment period. Such a slow recovery is inconsistent with the notion that market prices quickly reflect relevant information.